2016
DOI: 10.1111/bjso.12144
|View full text |Cite
|
Sign up to set email alerts
|

Being smart or getting smarter: Implicit theory of intelligence moderates stereotype threat and stereotype lift effects

Abstract: This research explores implicit theory of intelligence (TOI) as a moderator of stereotype activation effects on test performance for members of negatively stereotyped and of favourably stereotyped groups. In Germany, Turkish-origin migrants are stereotyped as low in verbal ability. We predicted that on a test diagnostic of verbal intelligence, endorsement of an entity TOI predicts stereotype threat effects for Turkish-origin students and stereotype lift effects for German students. This effect could account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 55 publications
2
30
1
Order By: Relevance
“…We contribute to the existing research literature on stereotype threat effects for migrants (e.g., Appel et al, 2015;Froehlich, Martiny, Deaux, Goetz, et al, 2016;Martiny et al, 2015) by revealing that vertical collectivism interacts with the activation of negatives stereotypes on performance and individual mobility motivation. Our findings are also relevant to work on the relationship between individual differences in student characteristics and achievement-related outcomes (e.g., Jurik et al, 2014) revealing that migrant students with high vertical collectivism endorsement suffer from stereotype threat effects.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…We contribute to the existing research literature on stereotype threat effects for migrants (e.g., Appel et al, 2015;Froehlich, Martiny, Deaux, Goetz, et al, 2016;Martiny et al, 2015) by revealing that vertical collectivism interacts with the activation of negatives stereotypes on performance and individual mobility motivation. Our findings are also relevant to work on the relationship between individual differences in student characteristics and achievement-related outcomes (e.g., Jurik et al, 2014) revealing that migrant students with high vertical collectivism endorsement suffer from stereotype threat effects.…”
Section: Resultsmentioning
confidence: 75%
“…This effect has also been shown for Turkish-origin students in Germany (Froehlich, Martiny, Deaux, Goetz et al, 2016;Martiny et al, 2015) and thus might contribute to the observed performance differences between German and Turkish-origin students (e.g., Martiny, Götz, & Keller, 2013;Schauenburg, 2011;Schofield, 2006;Strasser, 2012). However, the effect of stereotype threat for Turkish-origin students may depend on individual students' cultural value orientation.…”
Section: Vertical Collectivism and Stereotype Threatmentioning
confidence: 75%
See 1 more Smart Citation
“…This means that whenever people are reminded of a stereotype, a negative stereotype is activated for one group (e.g., female soccer players), but a positive stereotype is activated for another group (e.g., male soccer players). Research shows that when a person is reminded that others are negatively stereotyped (i.e., a negative outgroup stereotype), through social comparison to the denigrated group, that person's performance may be heightened (Chalabaev, Stone, Sarrazin, & STEREOTYPE THREAT IN SPORT Croizet, 2008;Froehlich, Martiny, Deaux, Goetz, & Mok, 2016;Laurin, 2013). This is known as stereotype lift (Walton & Cohen, 2003).…”
Section: Effects Of Positive Stereotypesmentioning
confidence: 99%
“…If people conceive intelligence as fixed (i.e. hold an entity theory), they prefer performance goals; if they conceive intelligence as malleable (i.e., hold an incremental theory), they prefer learning goals and believe that they can expand intelligence by effort (7). Individuals, who believe intelligence is malleable (a growth mindset) are better able to bounce back from failures than those, who believe intelligence is immutable (8).…”
Section: Introductionmentioning
confidence: 99%